DESIGNING ENGLISH POSTER OF SIMPLE FUTURE TENSE FOR ELEVENTH GRADE STUDENTS OF SMKN 2 TARAKAN - Cisaruanda, Metric; Arifin, Arifin; Kusmaryani, Woro (Universitas Borneo Tarakan, 2022)
This research aims to design learning media for the XI class of State Vocational School 2 Tarakan. The research design was research and development (RD) using the ADDIE model; Analysis, Design, Development, Implementation, and Evaluation. Data were collected using some research instrument; document analysis, questionnaires, and interviews. This research was conducted from February 14, 2022, to June 6, 2022. The subjects of this research were students of the XI class consisting of 87 students. The results of this study indicated that it has succeeded in developing a product in the form of a simple future tense poster as a learning medium for class XI SMKN 2 Tarakan. Then, the poster was validated by design expert, content. The quality of the posters from the design experts was â€œgoodâ€ with a percentage of 88%, those from the content experts were also good based on Core and basic competence, and the language aspect was also good category with percentage of 89%. Furthermore, student response to poster media is â€œgoodâ€, with a percentage of 81%. Therefore, students are interested in learning English with poster media. Thus, it can be concluded that submitting simple future tense posters as a learning media for XI class State Vocational School 2 Tarakan increases student interest in learning English, especially tenses.